2014
DOI: 10.1080/13218719.2014.919688
|View full text |Cite
|
Sign up to set email alerts
|

Line-up Member Similarity Influences the Effectiveness of a Salient Rejection Option for Eyewitnesses

Abstract: Visually salient line-up rejection options have not been systematically studied with adult eyewitnesses. We explored the impact of using a non-verbal, salient rejection option on adults' identification accuracy for line-ups containing low-or high-similarity fillers. The non-verbal, salient rejection option had minimal impact on accuracy in low-similarity lineups, but in high-similarity line-ups its inclusion increased correct rejections for target-absent line-ups as well as incorrect rejections in target-prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
(44 reference statements)
0
16
1
Order By: Relevance
“…(2014) used simultaneous photo lineups, the procedure utilized in the US. The serial presentation used in the current study may have resulted in higher rates of accuracy for the younger adults in the control TA condition of the current study, as compared to the study by Bruer et al (2014). A further difference is that the current study implemented a longer delay of 1-2 days between seeing the mock crime and then viewing the lineup, compared to Bruer at al.…”
Section: The Mystery Man Silhouettecontrasting
confidence: 44%
See 2 more Smart Citations
“…(2014) used simultaneous photo lineups, the procedure utilized in the US. The serial presentation used in the current study may have resulted in higher rates of accuracy for the younger adults in the control TA condition of the current study, as compared to the study by Bruer et al (2014). A further difference is that the current study implemented a longer delay of 1-2 days between seeing the mock crime and then viewing the lineup, compared to Bruer at al.…”
Section: The Mystery Man Silhouettecontrasting
confidence: 44%
“…Bruer, Fitzgerald, Therrien and Price (2014) found that although the silhouette increased correct rejections for TA lineups, this benefit was offset by a reduction in correct identifications for TP lineups. Bruer et al (2014) suggested that using the silhouette made the option to reject the lineup more salient, which was beneficial for TA lineups, but had the detriment that it also increased rejections for TP lineups. They proposed that the costs of using the silhouette outweighed its benefits with young adult participants.…”
Section: Using a Silhouette As An Additional Option In A Lineupmentioning
confidence: 98%
See 1 more Smart Citation
“…More recently, Bruer, Fitzgerald, Therrien, and Price (2015) wanted to examine the effect of a salient rejection option on identification accuracy across lineups varying in foil similarity. To test this, the researchers constructed high and low similarity lineups using similarity ratings provided by judges who were independent of the main study.…”
Section: Lineup Presentation and Foil Similaritymentioning
confidence: 99%
“…Research examining the effect of foil similarity and lineup procedure on eyewitness identification accuracy has primarily utilized the simultaneous or sequential lineup procedures. However, one study was recently conducted using the wildcard procedure (i.e., a salient rejection option; Bruer et al, 2015). As various other procedures, such as the elimination-plus procedure, have begun to be empirically studied, it is important to further examine the potential effect that these lineups may have in combination with foil similarity on overall identification abilities.…”
Section: Overview Of the Current Studymentioning
confidence: 99%